2020
DOI: 10.7554/elife.51480
|View full text |Cite
|
Sign up to set email alerts
|

Novel insights into breast cancer copy number genetic heterogeneity revealed by single-cell genome sequencing

Abstract: Copy number alterations (CNAs) play an important role in molding the genomes of breast cancers and have been shown to be clinically useful for prognostic and therapeutic purposes. However, our knowledge of intra-tumoral genetic heterogeneity of this important class of somatic alterations is limited. Here, using single-cell sequencing, we comprehensively map out the facets of copy number alteration heterogeneity in a cohort of breast cancer tumors. Ou/var/www/html/elife/12-05-2020/backup/r analyses reveal: gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 61 publications
5
48
0
Order By: Relevance
“…In this respect, it is noteworthy that MYC amplifications in human PDAC were far more common in metastases than primary tumors, including one case in which we were able to trace a metastatic lesion directly to a MYC-amplified subclone in the primary tumor. Collectively, these results suggest that subclonal MYC amplifications, which have been observed in human primary tumors, provide a selective advantage during metastatic progression (70,71). As one of the best-studied oncogenes, MYC has been associated with multiple tumorpromoting activities (67).…”
Section: Discussionmentioning
confidence: 82%
“…In this respect, it is noteworthy that MYC amplifications in human PDAC were far more common in metastases than primary tumors, including one case in which we were able to trace a metastatic lesion directly to a MYC-amplified subclone in the primary tumor. Collectively, these results suggest that subclonal MYC amplifications, which have been observed in human primary tumors, provide a selective advantage during metastatic progression (70,71). As one of the best-studied oncogenes, MYC has been associated with multiple tumorpromoting activities (67).…”
Section: Discussionmentioning
confidence: 82%
“…Beyond assessing the transcriptome, single-cell DNA sequencing approaches have been developed and used to identify subpopulations of cells that express unique mutational and CNA patterns in therapeutically actionable genes in a given breast tumor [ 224 ]. These findings have clear clinical implications as different subpopulations will be likely be uniquely sensitive or resistant to specific therapeutic regimens and contribute to the evolution of the tumor and therapeutic sensitivity.…”
Section: Advances In Genomic Analyses Of Breast and Ovarian Cancermentioning
confidence: 99%
“…Moreover, sequencing studies highlighted the genetic differences between primary tumors and metastases [21]. Genomic studies at single cell level showed profound genetic heterogeneity and extensive clonal diversity in breast cancer [22,23], as well as heterogeneity in copy number alterations of genes and regions with known biological relevance in breast cancer, such as genes associated with metastasis and therapeutic response [24].…”
Section: Genomic Indications Of Tumor Heterogeneitymentioning
confidence: 99%